The agency of fertility plans - Bazzani, Giacomo; Vignoli, Daniele (Frontiers in Sociology, 2022)
Fertility plans are a prominent area for agency research, and are a clear example of a misalignment between resources and agency capacity. We relied both on the idea of conversion factors of the Capability Approach and the pragmatist tradition of temporal-oriented agency to propose a framework for the study of fertility agency as the conversion process of resources into plans and behavior. We outlined said framework by using a unique dataset on fertility plans composed of open and closed questions from an Italian sample. Economic factors and imaginaries related to children and family represented the vast majority of (hindering and enabling) conversion factors. The notion of conversion factors is crucial for disentangling the network of heterogeneous elements involved in fertility agency: it allows focus to be shifted from structural factors related to social position and psychological characteristics to more situated elements that enable agency capacity.